One-stage vs. two-stage bilateral total hip arthroplasty: no difference in clinical outcomes, complications and revision rates in at 5-year follow up - Monzio Compagnoni, Alessandra; Montagna, Alice; Accatino, Giada; Benazzo, Francesco; Mosconi, Mario; Saracco, Michela; Grassi, Federico Alberto; Jannelli, Eugenio (Frontiers in Surgery, 2025)
Background/objectivesTotal hip arthroplasty (THA) is an effective treatment for end-stage hip disorders, improving pain, function, and quality of life. For bilateral hip disease, choosing between one-stage (simultaneous) and two-stage (staged) bilateral THA is critical. One-stage THA may reduce hospitalization but carries higher risks. This study evaluates whether one-stage bilateral THA is non-inferior to two-stage THA in safety and functional recovery.MethodsA retrospective study of patients undergoing bilateral THA between January 2010 and November 2019 compared one-stage (84 patients) and two-stage (63 patients) procedures. Surgeries used a postero-lateral approach with H-Max and DeltaTT implants. Outcomes included pain (VAS), function (Oxford Hip Score, EQ-5D, Forgotten Joint Score), and complications. Follow-ups were conducted at 1, 3, and 6 months, and at 5 years for both groups.ResultsBoth groups showed significant improvements in pain and function scores with no differences between them. Forgotten Joint Score was also comparable. Complications, including urinary infections and hematomas, were similar, and no revisions occurred in the one-stage group, compared to a 1.6% revision rate in the two-stage group. Hemoglobin decrease and transfusion rates were comparable.ConclusionsBoth approaches resulted in improved symptoms and quality of life with similar complication rates. The one-stage group had fewer complications and no revisions, suggesting potential cost savings. These findings support the safety of one-stage bilateral THA, emphasizing the need for careful patient selection and surgical expertise.